Dried Blood Spot Sampling with LC-MS Analysis for Routine Therapeutic Caffeine Monitoring in Neonates. (20th November 2012) - Lawson, Graham; Patel, Parul; Mulla, Hussain; Tanna, Sangeeta
Abstract : A liquid chromatography-mass spectrometry (LC-MS) method was developed and validated for the determination of therapeutic levels of caffeine in dried blood spot (DBS) samples. Caffeine is used in the treatment of Apnoea of Prematurity (AoP) in newborn children. Calibration DBS samples were prepared by spotting 15  μ L of whole blood spiked with the analyte onto specimen collection cards. 3 mm disks cut from the centre of the DBS were extracted in methanol containing the internal standard. The extract was separated using a Zorbax Eclipse Plus C18 column and the MS, operated in electrospray positive ion mode, used single ion monitoring at m/z 195 for caffeine and m/z 198 for the IS. The overall extraction recovery of caffeine from spiked blood spots was demonstrated to be 44–47%. Validation of the microanalytical method showed good precision (coefficient of variation) and accuracy (relative error) and specificity and was linear within the tested calibration range 500–25000 ng/mL for caffeine. Investigation of different specimen collection papers revealed different matrix effects with significant ion suppression from the FTA Elute paper itself. Requiring only a microvolume (15  μ L) blood sample for analysis, the developed DBS based microanalytical method has the potential to facilitate the routine monitoring of caffeine in neonates.